Liên hiệp thư viện Việt Nam về nguồn tin điện tử: cần làm gì để tiếp tục phát triển? - Trần, Thị Hải Yến (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents the formation, legal basis, member structure, activity mechanism and information resources of Vietnam Library Consortium for Electronic Resources;sets forth measures for  continuing the development of this organization.